Autonomous Navigation System for a Wall-painting Robot based on Map Corners - Soares, João Carlos; Abati, Gabriel; Lima, Gustavo Henrique; Meggiolaro, Marco Antonio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
Wall-painting is an important task in construction that has an increasing necessity for automation. This paper presents a navigation system for a wall-painting robot based on map corners. Using an occupancy grid map as input of the system, the proposed method is able to generate a path following the walls of the environment. The main advantage of the proposed methodology is the ability to work in non-convex and open maps. The system is implemented as a ROS package and is integrated with the ROS navigation stack. The method is tested in a simulator developed using ROS and Gazebo, a virtual environment that simulates the physics and dynamics of robotic systems.